Flow pattern around traditional malay house using enhanced smoke wire technique in a boundary layer wind tunnel - Kamil Khalili, Haji Abdullah; Nurizzatul Atikha, Rahmat; Khairun Adhani, Khairunizam (Institution of Engineering and Technology, 2022)
Traditional Malay houses are well-known for their excellent natural ventilation. The claim was supported in a study which compared the temperature measurements in traditional Malay houses with temperature measurements in modern homes. However, few flow pattern studies have proven this fact. This paper aims to understand this phenomenon qualitatively by utilising smoke lines produced by the smoke wire technique to observe the flow pattern around a single model traditional Malay house mounted over a smooth plate in a small-scaled quasi-atmospheric boundary layer wind tunnel. Observation of the conventional model house has highlighted several common and unique flow patterns from the high-speed footage. The smoke visualisation technique will provide flow visualisation and capture using a high-speed camera at 1000 fps. In addition, the paper also focuses on developing improvements for the smoke-wire technique system by upgrading the controlled drip valve and adding a tensioner system. Limitations and the ideal conditions have been recorded for the smoke-wire technique, which improved the overall quality of the observation. The models were used did not have any opening or only a single opening has started to show good natural ventilation. However, having only inlets for the airflow has failed to show observable good natural ventilation.